2020
DOI: 10.1016/j.radonc.2019.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Repeat stereotactic body radiation therapy (SBRT) for salvage of isolated local recurrence after definitive lung SBRT

Abstract: Purpose: Optimal management of isolated local recurrences after stereotactic body radiation therapy (SBRT) for early non-small cell lung cancer (NSCLC) is unknown and literature describing repeat SBRT for in-field recurrences after initial SBRT are sparse. We investigate the safety and efficacy of salvage SBRT for isolated local failures after initial SBRT for NSCLC.Methods/Materials: Patients receiving SBRT for isolated local recurrence after initial SBRT for early NSCLC were identified using a prospective re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 44 publications
(54 reference statements)
0
20
0
Order By: Relevance
“…The reported OS, PFS and local control at three years for NSCLC patients was 27%, 40%, and 40%, respectively, for central location and 31%, 25%, and 52%, respectively, for peripheral location, with no toxicity graded 3 or higher reported (84). Smaller studies have reported comparable results (93)(94)(95)(96)(97)(98)(99). The available data suggests that salvage SBRT with BED >100 Gy 10 appears to be well tolerated and safely applicable in carefully selected patients with peripheral tumor location; repeat SBRT should be evaluated only very carefully in centrally located tumors (95).…”
Section: Patients With Local Recurrence After Initial Sbrtmentioning
confidence: 94%
“…The reported OS, PFS and local control at three years for NSCLC patients was 27%, 40%, and 40%, respectively, for central location and 31%, 25%, and 52%, respectively, for peripheral location, with no toxicity graded 3 or higher reported (84). Smaller studies have reported comparable results (93)(94)(95)(96)(97)(98)(99). The available data suggests that salvage SBRT with BED >100 Gy 10 appears to be well tolerated and safely applicable in carefully selected patients with peripheral tumor location; repeat SBRT should be evaluated only very carefully in centrally located tumors (95).…”
Section: Patients With Local Recurrence After Initial Sbrtmentioning
confidence: 94%
“…Although variations in the extent of dose overlap (e.g., within 1 cm of the original field versus >1 cm) among these studies are probably a source of selection bias, the principles of repeat SABR are similar to those for primary disease treatment, including the need to consider the size and location of the disease, tumor motion, high-quality image guidance, and delivery of biologically effective doses (BEDs) of greater than 100 Gy (although whether higher BEDs are required for recurrent disease remains controversial). 12,46,[52][53][54] Overall, repeat SABR has led to excellent rates of short-term local control (nearly 90%), acceptable rates of regional control (>80%), and relatively low rates of grade 3 or greater events (<10%) (Table 2). 12,28,41,46,52,[55][56][57] The dosimetric objectives, however, for repeat SABR remain somewhat unclear.…”
Section: Repeat Sabrmentioning
confidence: 99%
“…12,46,[52][53][54] Overall, repeat SABR has led to excellent rates of short-term local control (nearly 90%), acceptable rates of regional control (>80%), and relatively low rates of grade 3 or greater events (<10%) (Table 2). 12,28,41,46,52,[55][56][57] The dosimetric objectives, however, for repeat SABR remain somewhat unclear. Toxic effects seem to be correlated with the composite dose to mediastinal structures and unirradiated lung, rather than the dose received by lung volumes previously treated to high doses.…”
Section: Repeat Sabrmentioning
confidence: 99%
“…Few studies analysed the rare scenario, where a second SBRT course was applied for in-field local recurrences or second primaries in the lung (supplementary table 2) [12][13][14]23 . In the absence of a common definition of "re-irradiation" in these studies, only Peulen et al used a definition based upon target volume overlap as in the present study.…”
Section: Discussionmentioning
confidence: 99%